Impact of Lower Screening TSH Cutoff Level on the Increasing Prevalence of Congenital Hypothyroidism - Violeta Anastasovska; Mirjana Kocova (International Journal of Neonatal Screening, 2017)
Lower cutoff levels in screening programs have led to an increase in the proportion of detected cases of transient hypothyroidism, leading to an increase in the overall prevalence of primary congenital hypothyroidism (CH) in several countries. We have performed a retrospective evaluation on the data from 251,008 (96.72%) neonates screened for thyroid-stimulating hormone (TSH) level in dried blood spot specimens taken 48 h after birth, between 2002 and 2015, using the DELFIA method. A TSH value of 15 mIU/L whole blood was used as the cutoff point until 2010 and 10 mIU/L thereafter. Primary CH was detected in 127 newborns (1/1976) of which 81.1% had permanent and 18.9% had transient CH. The prevalence of primary CH increased from 1/2489 before 2010 to 1/1585 thereafter (p = 0.131). However, the prevalence of permanent CH increased only slightly (p = 0.922), while the transient CH prevalence showed an 8-fold increase after lowering the TSH cutoff level (p < 0.001). In cases of permanent CH, we observed a lower prevalence of thyroid dysgenesis (82.7% vs. 66.7%) and a higher prevalence of a normal in situ thyroid gland (17.3% vs. 33.3%), for the period with a lower TSH cutoff value. Our findings support the impact of a lower TSH cutoff on the increasing prevalence of congenital hypothyroidism.